Preconcentration of seleno-amino acids on a XAD resin and determination in regional olive oils by SPE UPLC-ESI-MS/MS - Torres, Alberto Sabier (2014)
This study describes a method for seleno-amino acids determination in Argentinean olive oils. Preliminary total selenium determination in olive oils probed low concentrations (62.8±1.6 to 117.4±3.0 μg/kg) and the necessity of implementing a preconcentration method. To this end a XAD® resin was employed as sorbent for selenomethionine (Se-Met), selenomethylselenocysteine (Se-MetSeCys), and selenocysteine (Se-Cys) preconcentration. Determinations were performed by UPLC-ESI-MS/MS. Recoveries were between 84% and 97% for the seleno-amino acids studied, reaching a detection limit of 0.09 μg/kg, a precision of 10% (RSD, n=6), and an enhancement factor of 60-fold (6 for the extraction system and 10 for the preconcentration approach). The only detected Se species in the olive oils was Se-MetSeCys in concentrations ranging from 2.0 to 8.3 μg/kg.